Evaluation of pseudoprogression rates and tumor progression patterns in a phase III trial of bevacizumab plus radiotherapy/temozolomide for newly diagnosed glioblastoma - Wick, Wolfgang; Bendszus, Martin (Neuro-Oncology, 2016)
BackgroundEvaluation of glioblastoma disease status may be complicated by treatment-induced changes and discordance between enhancing and nonenhancing MRI. Exploratory analyses are presented (prospectively assessed pseudoprogression and therapy-related tumor pattern changes) from the AVAglio trial (bevacizumab or placebo plus radiotherapy/temozolomide for newly diagnosed glioblastoma).MethodsMRI was done every 8 weeks (beginning 4 wk after chemoradiotherapy) using prespecified and standardized T1 and T2 protocols. Progressive disease (PD) at 10 weeks was reconfirmed at 18 weeks to distinguish pseudoprogression. Progression-free survival (PFS), excluding cases of confirmed pseudoprogression, was assessed (post-hoc/exploratory). Tumor progression patterns were determined at each disease assessment/PD (prespecified/exploratory).ResultsOf patients with PD in the bevacizumab and placebo arms, 143/354 (40.4%) and 155/387 (40.1%), respectively, had PD due to contrast-enhancing lesions, and 51/354 (14.4%) and 53/387 (13.7%) had PD due to nonenhancing lesions. Of all patients in the bevacizumab arm (n = 458), 2.2% had confirmed pseudoprogression versus 9.3% in the placebo arm (n = 463). Baseline characteristics did not differ between patients with/without pseudoprogression (including for MGMT status). Excluding confirmed pseudoprogression, PFS (hazard ratio: 0.65, 95% CI: 0.56-0.75; P < .0001, bevacizumab vs placebo) was comparable to the intent-to-treat population. At PD, most patients had the same tumor focus (local/multifocal, >84%) and infiltrative profile (>88%) as at baseline; no shift to a diffuse or multifocal phenotype was observed.ConclusionsPseudoprogression complicated progression assessment in a small but relevant number of patients but had negligible impact on PFS. Bevacizumab did not appear to adversely impact tumor progression patterns.